THE ROLE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN FORMING STUDENT SOLIDARITY BASED ON SOCIAL HORRIBLE AND HARMONY (SDN 20 BATANG-TARANG) - Tanurianti, Siti; Sukino, Sukino; Usman, Usman (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2023)
The title of this research is The Role of Islamic Religious Education Teachers in Forming Student Solidarity Based on Harmony and Social Harmony (SD Negeri 20 Batang-Tarang). The purpose of this research is to create a peaceful and peaceful teaching and learning atmosphere, teachers are obliged to instill a sense of solidarity in their students. The formation of a sense of solidarity with these students seeks to form good character and harmony between students to create a harmonious learning atmosphere and avoid various kinds of conflict. The research method that researchers use is descriptive qualitative by using data collection techniques using interviews, documentation, and observation. The results of this study explain that the role of Islamic Religious Education teachers as coaches, mentors, and motivators of solidarity among students at SDN 20 Batang-Tarang is very well documented. When making observations at school, researchers received information that the Islamic Religious Education teacher had tried his best to be able to foster and guide his students by carrying out activities that lead to solidarity between students such as group discussions. In addition, the PAI teacher also always evaluates the work of students and praises and gives awards to their students, if the student has achievements, and provides sanctions that educate if there are students who are not orderly, irresponsible, and disobey the rules when carrying out learning.